Atractylodes macrocephala Koidz. volatile oil relieves acute ulcerative colitis via regulating gut microbiota and gut microbiota metabolism - Cheng, Hao; Zhang, Dandan; Wu, Jing; Liu, Juan; Tan, Yuzhu; Feng, Wuwen; Peng, Cheng (Frontiers in Immunology, 2023)
Background Atractylodes macrocephala Koidz. (AM) is a functional food with strong ant-colitis activity. AM volatile oil (AVO) is the main active ingredient of AM. However, no study has investigated the improvement effect of AVO on ulcerative colitis (UC) and the bioactivity mechanism also remains unknown. Here, we investigated whether AVO has ameliorative activity on acute colitis mice and its mechanism from the perspective of gut microbiota. Methods Acute UC was induced in C57BL/6 mice by dextran sulfate sodium and treated with the AVO. Body weight, colon length, colon tissue pathology, and so on were assessed. The gut microbiota composition was profiled using 16s rRNA sequencing and global metabolomic profiling of the feces was performed. The results showed that AVO can alleviate bloody diarrhea, colon damage, and colon inflammation in colitis mice. In addition, AVO decreased potentially harmful bacteria (Turicibacter, Parasutterella, and Erysipelatoclostridium) and enriched potentially beneficial bacteria (Enterorhabdus, Parvibacter, and Akkermansia). Metabolomics disclosed that AVO altered gut microbiota metabolism by regulating 56 gut microbiota metabolites involved in 102 KEGG pathways. Among these KEGG pathways, many metabolism pathways play an important role in maintaining intestine homeostasis, such as amino acid metabolism (especially tryptophan metabolism), bile acids metabolism, and retinol metabolism. Conclusion In conclusion, our study indicated that AVO can be expected as novel prebiotics to treat ulcerative colitis, and modulating the composition and metabolism of gut microbiota may be its pharmacological mechanism.